Scroll and Shop: Exploring Online Shopping Culture in the Digital Media Era - Khoiruddin Muchtar; Nunung Nurhasanah; Moch Fakhruroji (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
The purpose of this paper is to describe the phenomenon of widespread use of online shopping platforms, which is framed as consumption behavior in media culture. The phenomenological method was used in this study, which involved four informants who were interviewed in-depth about their experiences with online shopping platforms. According to the studies, even though informants could use online shopping applications, some still saw it as an alternative to traditional shopping practices. In contrast, others indicated that online shopping had become their daily behavior. Additionally, the study highlights that although informants recognize the benefits and convenience of online shopping, they are also aware of its drawbacks. This awareness underscores the need for consumers to be cognizant of the risks associated with online shopping activities. As online shopping becomes increasingly popular, it remains essential to carefully consider its advantages and disadvantages to avoid potential problems. Overall, the study provides insights into how online shopping is perceived and utilized, emphasizing the importance of balancing its benefits with the awareness of its inherent risks.